Secondary succession of shrub-herb communities in the hilly area of Taihang Mountain - Liu, Xiuping; Zhou, Wangming; Li, Xiaoxin; Zhang, Yuming; Dong, Wenxu (Frontiers in plant science, 2023)
IntroductionTo document the successional processes of shrub-herb communities after large-scale human disturbance, and understand how changing environmental conditions affect species replacement in semi-humid hilly areas.MethodsUtilizing the established permanent plots in the hilly area of Taihang Mountain, we evaluated temporal patterns of vegetation and soil following grass-to-shrub succession.Results and DiscussionAlong secondary succession, Vitex negundo var. heterophylla gradually dominated in dry sunny slope and shared the dominance with Leptodermis oblonga in shaded slope. Herbaceous dominant species in shrub-herb communities switched from Themeda japonica , Bothriochloa ischaemum , Artemisia sacrorum , and Cleistogenes chinensis in 1986 census to B . ischaemum and A . sacrorum in 2008 census, but herb was no longer dominant in 2020 census. As succession progresses, species dominance increased while richness decreased generally, and herb cover and aboveground biomass decreased, whereas shrub height, cover, and aboveground biomass increased significantly. Soil organic matter (SOM), total nitrogen (TN), total phosphorus (TP), and total potassium (TK) in topsoil increased significantly while pH declined by 1.04 units over the past three decades. Plant communities transitioned from perennial herbs to shrub-herb and then shrub communities, and V . negundo var. heterophylla dominated in the succession of shrub-herb communities. Climate and soil properties, combined with plant attributes, together drive post-disturbance secondary succession. From a management perspective, the tight coupling between vegetation and soil under local climatic conditions should be considered to improve the fragile ecosystem in the hilly area of Taihang Mountain.